ANALISIS SISTEM INFORMASI AKUNTANSI DAN PENGENDALIAN INTERNAL PERSEDIAAN BAHAN BAKU PADA JENGKI COFFEE DI SURABAYA - Sunia Apriyono; Hwihanus Hwihanus (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2023)
The accounting system is a tool used to organize or collect, collect, and conduct information regarding all company transactions, where employees, company activities, materials and machines can be integrated in such a way that supervision can be carried out. This study aims to find out how to analyze information systems and internal control of raw material supplies at the JENGKI Coffee shop in SURABAYA. The data used are qualitative data in the form of some basic analysis from field interviews. The results showed that the Jengki Coffee Shop has good supply chain management capabilities as evidenced by the existence of suppliers who have long-term cooperative relationships with them.